Perkawinan Antar Agama: Studi Fatwa MUI Nomor: 4/Munas VII/MUI/8/2005, Kompilasi Hukum Islam dan UU No. 1 Tahun 1974 - Muhammad Habibul Amin; Sukiati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The issue of inter-religious marriage continues to be a concern among Islamic thinkers until now, becoming a discussion that does not recede, in line with the practice of such marriages which are still common among Muslims in Indonesia. The purpose of this article is to explain the status of inter-religious marriages in the perspective of Islamic law and legislation in Indonesia. This research utilizes a qualitative method using data sources from the literature (library research), which involves the collection, analysis, and interpretation of a comprehensive narrative of literature data to gain a thorough, comprehensive, and holistic understanding of the status of interfaith marriage in Indonesia. The results show that the Indonesian Ulema Council (MUI) has circulated a Fatwa stating that it is forbidden for Muslims, both men and women, to marry non-Muslims, including those who are People of the Book. The rationale for the Fatwa is that inter-religious marriages often cause conflicts in society and trigger conflicts of debate among Muslims. MUI's view is in accordance with the provisions of Law No. 1/1974 on Marriage and the Compilation of Islamic Law which also prohibit marriage between adherents of different religions.